In a uniformly assessing accelerating motion, the velocity of this specific object follows the law:
v(t) = v₀ + at
where v₀ is the initial velocity, followed by an acceleration and t stands for time.
In the given question statement, the robot starts from rest such that the initial speech achieved is zero where,
vi = 0
Now, the robot undergoes a free fall such that the acceleration is assumed as the gravitational acceleration given the,
g= 9.81m/s².
Therefore, along with the time t = 3.5s and the velocity is,
v(3.5) = 0 + (9.81m/s²) (3.5s) = 34.4m/s
Hence, the speech after it has fallen accounts for 34.3 m/s
Learn more about acceleration here,
https://brainly.com/question/12550364
# SPJ4